Penyimpangan Praktik Pernikahan Semarga dalam Adat Batak Mandailing di Kabupaten Mandailing Natal (Realitas, Faktor Penyebab, dan Pergeseran Norma) - Rangkuti, Muhammad Yusuf; Muhammad Hafizh; Mohd Zaidi Daud (UIN Sunan Kalijaga Yogyakarta, 2024)
The prohibition of marriage within the same clan (marga) in Batak Mandailing tradition is traditionally forbidden as it is considered a form of consanguineous marriage based on patrilineal descent and is not recognized by customary law. However, with the passage of time, there has been a shift in meaning and changes in societal attitudes towards this prohibition, particularly in Mandailing Natal Regency, North Sumatra. This study explores the factors influencing the shift in societal attitudes towards this prohibition, as well as its implications for customary law and cultural identity. Employing a qualitative approach with descriptive and comparative methods, data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that the prohibition aims to preserve lineage and prevent sibling marriages; however, instances of intra-clan marriages are beginning to occur due to factors such as love, religion, education, economy, and cultural changes. The novelty of this research lies in the identification of new factors influencing the shift in societal attitudes, as well as the challenges posed by the younger generation to traditional norms. These findings provide new insights into the transformation of customary law and cultural identity in a modern context. Perkawinan satu marga dalam adat Batak Mandailing secara tradisional dilarang karena dianggap sebagai bentuk perkawinan sedarah dari garis keturunan ayah (patrilineal) dan tidak diakui secara adat. Namun, seiring perkembangan zaman, terjadi pergeseran makna dan perubahan sikap masyarakat terhadap larangan ini, khususnya di Kabupaten Mandailing Natal, Sumatera Utara. Penelitian ini mengeksplorasi faktor-faktor yang mempengaruhi pergeseran sikap masyarakat terhadap larangan tersebut, serta implikasinya terhadap hukum adat dan identitas budaya. Menggunakan pendekatan kualitatif dengan metode deskriptif dan komparatif, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Hasil penelitian menunjukkan bahwa larangan ini bertujuan menjaga silsilah dan menghindari perkawinan antar saudara, namun praktik perkawinan semarga mulai terjadi karena faktor cinta, agama, pendidikan, ekonomi, dan perubahan budaya. Novelty penelitian ini terletak pada identifikasi faktor-faktor baru yang mempengaruhi perubahan sikap masyarakat, serta tantangan generasi muda terhadap norma tradisional. Temuan ini memberikan wawasan baru tentang transformasi hukum adat dan identitas budaya dalam konteks modern.